PENDIDIKAN PESANTREN: DARI DIKOTOMI MENJADI INTEGRASI KURIKULUM - Asmuki Asmuki (LP2M Universitas Ibrahimy, 2014)
PP. Salafiyah Syafi'iyah always holds and accepts to science and technology. Therefore, the curriculum of PP. Salafiyah Syafi'iyah is integrated between the kurikulum nasional (kurnas) and kurikulum lokal pesantren (kurlok). Integrated is both of the unit of educational pesantren contains those curriculum. Kurikulum lokal pesantren (kurlok) be taught in MI to Ma'had Aly, and kurikulum nasional (kurnas) from SD to university.